FRI0156 WORK PARTICIPATION IN PATIENTS WITH SYSTEMATIC LUPUS ERYTHEMATOSUS: A SYSTEMATIC REVIEW. (2nd June 2020) - Blomjous, B.; Gajadin, G.; Bultink, I.; Voskuyl, A.; Falzon, L.; Hoving, J.; Ter Wee, M.
Abstract : Background: The treatment of systemic lupus erythematosus (SLE) has improved over the last decades, however, absenteeism and work disability numbers remain higher than those observed in the general population (1). SLE has its onset between the ages of 20 and 40 years, and has a major burden on the lives of patients, both mentally and financially. A recent online survey amongst 2070 European SLE patients revealed that 69.5% of patients had their careers affected due to SLE (2). Objectives: To determine the magnitude of absenteeism and work disability in patients with SLE and to investigate the factors that might affect work participation in these patients in order to develop interventions to reduce the impact of the burden in the future. Methods: A systematic literature search was performed to identify published articles reporting on the prevalence of work related burden, as well as the relation of having SLE on employment status, sick leave and/or presenteeism. Full-text original articles (all languages) published before April 2019 were identified by literature search performed in MEDLINE, Cochrane, Embase and CINAHL. Results: In total, 2057 non-duplicate citations were screened after database searching and snowballing. Finally, 81 articles were included; most studies (n=59) had a cross-sectional design and the remaining 22 studies had a longitudinal design. Only 15 longitudinal cohort studies reported on associations, 6 studies described a longitudinal prediction model, 2 studies reported on associations and described a prediction model, and 3 studies had a longitudinal design but only reported on prevalences over time. In total, 3500 working patients were included in the studies reporting on associations or describing a longitudinal prediction model. In the association studies, the most frequently used outcome measures were respectively being employed/probability of being employed and work loss/job cessation. Other studies used loss of days from (non)workforce activities/sick leave days, work disability, productivity loss or work entry. Most associations with work outcome were found for demographic variables and two or three disease variables, like Systemic Lupus Activity Questionnaire (SLAQ) score and depressive symptoms. This was also the case in the prediction studies. Most studies did not assess work related variables as possible predictors for work outcome. Conclusion: A large heterogeneity was found in type of study design and outcome measures, which limits comparison with other studies. More longitudinal studies are needed to truly assess the impact of SLE on work participation, and to identify factors that could be influenced during interventions, in order to encourage work participation of these patients. References: [1]Bultink IE, Turkstra F, Dijkmans BA, Voskuyl AE. High prevalence of unemployment in patients with systemic lupus erythematosus: association with organ damage and health-related quality of life. J Rheumatol. 2008;35(6):1053-7. [2]Gordon C, Isenberg D, Lerstrom K, Norton Y, Nikai E, Pushparajah DS, et al. The substantial burden of systemic lupus erythematosus on the productivity and careers of patients: a European patient-driven online survey. Rheumatology (Oxford). 2013;52(12):2292-301. Disclosure of Interests: None declared